2003
DOI: 10.1159/000068891
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma Arising in a Radiotherapy Field: Report of Two Cases and Review of the Literature

Abstract: We report 2 patients who developed melanoma or melanoma metastases in radiation fields 6 and 43 years after radiation therapy, respectively. One of the patients had received adjuvant hyperfractionated photon therapy for Ewing sarcoma, while the other patient had received X-ray therapy for a hemangioma. While postradiation secondary cancers with a long latency period are not uncommon, the development of melanoma is exceedingly rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…In Austria, routine health data are usually available per district and UVR dose data only for nine locations. In the current study, we assumed a latency period for melanoma of at least 10 years based on the respective literature, with altitude and inter-annual variability as main predictors of melanoma risk-associated UVR exposure [27,28,29,30,31]. …”
Section: Instructionmentioning
confidence: 99%
“…In Austria, routine health data are usually available per district and UVR dose data only for nine locations. In the current study, we assumed a latency period for melanoma of at least 10 years based on the respective literature, with altitude and inter-annual variability as main predictors of melanoma risk-associated UVR exposure [27,28,29,30,31]. …”
Section: Instructionmentioning
confidence: 99%
“…In general, exposure categories with elevated risks of leukemia had an elevated risk for melanoma [9]. Trefzer et al reported two patients that developed melanoma or melanoma metastases within a radiated field, six and forty-three years after radiation therapy [10]. Similarly, Miracco et al reported two cases of unusual neoplasms secondary to radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to continue observations on the clinical course with attention paid to the development of secondary skin cancer [8] .…”
Section: Discussionmentioning
confidence: 99%